2013
DOI: 10.1186/2041-9139-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Left-right asymmetric expression of dpp in the mantle of gastropods correlates with asymmetric shell coiling

Abstract: BackgroundVarious shapes of gastropod shells have evolved ever since the Cambrian. Although theoretical analyses of morphogenesis exist, the molecular basis of shell development remains unclear. We compared expression patterns of the decapentaplegic (dpp) gene in the shell gland and mantle tissues at various developmental stages between coiled-shell and non-coiled-shell gastropods.ResultsWe analyzed the expression patterns of dpp for the two limpets Patella vulgata and Nipponacmea fuscoviridis, and for the dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The subsequent direction of shell coiling in later development seen in B. glabrata and L. stagnalis morphs also correlated with sidedness of gene expression. It has also been shown that asymmetric growth and torsion in larval snails is driven by TGF-b signaling (Kurita and Wada, 2011), with the TGF-b superfamily ligand Dpp (BMP2/4 or Decapentaplegic) suggested to integrate asymmetric cues in postembryonic shell morphogenesis through a gradient of Dpp in the shell gland (Shimizu et al, 2011(Shimizu et al, , 2013. Despite these advances, much remains unknown, with most studies only considering gastropod molluscs.…”
Section: Asymmetry In the Lophotrochozoamentioning
confidence: 99%
“…The subsequent direction of shell coiling in later development seen in B. glabrata and L. stagnalis morphs also correlated with sidedness of gene expression. It has also been shown that asymmetric growth and torsion in larval snails is driven by TGF-b signaling (Kurita and Wada, 2011), with the TGF-b superfamily ligand Dpp (BMP2/4 or Decapentaplegic) suggested to integrate asymmetric cues in postembryonic shell morphogenesis through a gradient of Dpp in the shell gland (Shimizu et al, 2011(Shimizu et al, , 2013. Despite these advances, much remains unknown, with most studies only considering gastropod molluscs.…”
Section: Asymmetry In the Lophotrochozoamentioning
confidence: 99%
“…Some developmental regulatory genes are expressed in the mantle epithelium that generates the shell (11)(12)(13)(14)(15)(16). The growth factor dpp/BMP2-4 has been implicated in mantle proliferation (17)(18)(19)(20)(21). In the bivalve Pinctada fucata, a gradient of proliferation perpendicular to the mantle edge has been reported, with generally higher proliferation in interior parts of the mantle and lower rates in zones near the outer edges (22).…”
mentioning
confidence: 99%
“…This is in stark contrast to the situation in L. stagnalis. Furthermore, while other research groups have previously reported WMISH expression patterns for several genes in L. stagnalis larvae (see 22,28,29 ) the method that we describe here yields patterns of significantly higher spatial resolution. Finally, we have observed significant inter-batch variation in the activity of the Proteinase-K from our supplier.…”
mentioning
confidence: 78%